Frozen Storybook Collection - Elias, Walter (UK Parragon Books Ltd, 2015)
Inside this beautiful book you'll find six magical adventures to enjoy. Read about the sister's trip across the sea, join Olaf on his perfect summer's day, meet a new reindeer friend, and lots more!
Shelving Location KG class. Fiction Stories
Keywords: English Fiction Book